A Social Network Analysis of Occupational Segregation - Sebastian Buhai; Marco van der Leij (Tinbergen Institute, 2006)
This paper proposes a simple social network model of occupational segregation, generated by the existence of inbreeding bias among individuals of the same social group. If network referrals are important in getting a job, then expected inbreeding bias in the social structure results in different career choices for individuals from different social groups, which further translates into stable occupational segregation equilibria within the labour market. Our framework can be regarded as complementary to existing discrimination or rational bias theories used to explain persistent observed occupational disparities between various social groups.
Keywords: A14; J31; J70; Z13; 330; Social Networks; Occupational Segregation; Labour Market